How do customers respond to the hotel servicescape?. (September 2019) - Lockwood, Andrew; Pyun, Kyunghee
Highlights: Only four of the five servicescape dimensions contribute to explaining 'Pleasure' and 'Arousal'. 'Spaciousness' was the most important dimension in predicting guests' 'Favourable behaviours'. None of the dimensions affected propensity to spend. Both 'Pleasure' and 'Arousal' had a positive influence on 'Favourable behaviours'. Only 'Pleasure' was found to be significant in the explanation of 'Propensity to spend'. Abstract: Previous research shows some links between customers' perceptions of their service experience in hotels, overall satisfaction and enhanced sales revenue. However, the ways in which the servicescape influences the customer and their perceptions of the hotel experience remains relatively unexplored. This study explores the links between customers' perceptions of the hotel servicescape and their emotional and behavioural responses. Previous research has used scales developed for other industrial contexts and this study aims to develop an instrument directly relevant to the hotel context. To achieve this goal, a recently developed hotel specific servicescape scale was used but both the emotional and behavioural response scales were developed based on existing research but expanded to include items specifically for hotel customers. Using a large-scale survey of hotel customers in London, analysis showed two dimensions of emotional responses and two dimensions of behavioural responses to be both valid and reliable for the hotel context. The study then successfully determined the relationship between five hotel servicescape dimensions and customers' emotional states and their behavioural responses. The findings showed the ways in which the hotel servicescape significantly affects both emotional and behavioural responses, having clear implications for both hotel design and management. The results also raised a number of interesting and potentially rewarding areas for further research.